Fintech System; Studi Hambatan Inklusi Keuangan UMKM di Kota Makassar - Anwar, Andi Faisal; Erwin, Erwin (ICOR: Journal of Regional Economics, 2021)
The purpose of this research is to find out and explain further, what are the obstacles to financial inclusion through the existence of a fintech system in Makassar City. And the results of this study are expected to be able to provide benefits to academics, lecturers, students and the government regarding the barriers to financial inclusion through the existence of a fintech system for MSMEs in Makassar City. This type of research used in this study is a type of quantitative research in which this research is an inquiry strategy that emphasizes the search for meaning, concepts, understandings, characteristics, symbols, symptoms, and descriptions of phenomena that are carried out in the Makassar City area. The data source of this research is to use primary and secondary data through interviews and data collection from various agencies in the form of documents and archives. So as for the results of this study it can be concluded that almost all of the informants are still unfamiliar with the lending process as such, there are several obstacles which then cause MSME entrepreneurs not to use or use the lending mode other than because they are afraid to deal with such lending, they also feel they do not know in detail about the procedural and procedures for using android-based loan services and technology. This is due to several obstacles including business actors who have not received clear information either through the media or through massive and direct socialization by the lending service providers so that businesses are still hesitant to use technology-based lending services, not to mention a lot of slanted news circulating among business actors for insecurity, that is, those from providers of technology-based lending services cannot guarantee the privacy of customers when borrowing money through technology-based applications, many assume that fraud often occurs when using instant technology-based lending services. then increasing the doubts of business actors. Keywords: Financial Inclusion, MSME, Fintech System.